Biological differences between focal and diffuse adenomyosis and response to hormonal treatment. Issue 4 (April 2019) - Khan, Khaleque N; Fujishita, Akira; Koshiba, Akemi; Mori, Taisuke; Kuroboshi, Haruo; Ogi, Hiroshi; Itoh, Kyoko; Nakashima, Masahiro; Kitawaki, Jo
Abstract: Research question: Is there any difference in ovarian steroid receptor expression and pattern of fibrosis in focal and diffuse adenomyosis and response to hormonal treatment? Design: Prospective controlled study where biopsy samples were prospectively collected after surgery from 30 women with focal adenomyosis, 21 women with diffuse adenomyosis and 20 women with uterine myoma. Some of these women underwent 3–6 months of treatment with gonadotrophin-releasing hormone agonist (GnRHa) before surgery. Tissue expression of oestrogen receptor (ER) and progesterone receptor (PR) was analysed by immunohistochemistry. Distribution of tissue fibrosis was examined by Masson's trichrome staining with computer-based image analysis of fibrosis in tissues derived from women with and without adenomyosis. Results: There was no difference in ER/PR expression in gland cells/stromal cells of adenomyotic lesions on the ipsilateral side of focal adenomyosis and the anterior/posterior walls of diffuse adenomyosis. Compared to myoma tissues, a relatively decreased expression of ovarian steroid receptors was observed in both focal and diffuse adenomyosis. Image analysis of tissue fibrosis indicated more fibrosis in both focal and diffuse adenomyosis compared to fibrosis in the myometrium derived from women with uterine myoma. The pattern of fibrosis was no different in tissues derived from GnRHa-treated and -untreated women with focal and diffuse adenomyosis. Conclusions: No difference was found in the expression of ER/PR and entity of fibrosis between women with focal and diffuse adenomyosis regardless of GnRHa treatment. A lower expression of ER/PR compared to myoma tissue potentially clarifies the biological rationale of non-response to hormonal therapies for adenomyosis.